(untitled) (Clinics, 2011)
BACKGROUND: Cognitive impairment, from mild forms to dementia, is an important social and health concern, principally among older individuals. Elderly patients are usually followed by general internists, who may overlook this condition. OBJECTIVE: Our aim was to determine whether cognitive impairment diagnosed by specialists had been previously detected by general internists. SUBJECTS AND METHODS: A total of 248 elderly individuals randomly selected from a list of outpatients seen by general internists in a public university hospital in São Paulo, Brazil, were evaluated by a geriatrician. Patients were then classified as having probable cognitive impairment or not, based on their performance on the Mini-Mental State Examination and the Informant Questionnaire on Cognitive Decline in the Elderly. Cases of probable impairment were submitted to routine laboratory investigation, brain computed tomography, and neuropsychological evaluation. The final diagnoses were established by a consensus panel comprising two neurologists and the geriatrician who evaluated the patients using all available data. General internists' files for all cognitively impaired cases and for a selected sample of individuals without cognitive impairment were checked for any record of cognitive complaints or decline. RESULTS: Forty-three patients were classified as demented (n = 21) or as cognitively impaired but not demented (n = 22). The evaluation of the general internists' files revealed that information on cognitive complaints or decline was recorded for seven (16.3%) of the 43 patients with dementia or cognitive impairment without dementia. CONCLUSIONS: General internists seldom detected cognitive decline in elderly patients in Brazil. Further studies should be conducted to elucidate the reasons for this low rate of detection.